Fixed point theorems for multivalued generalized nonlinear contractive maps in partial metric spaces - Aghajani, A.; Allahyari, K. (Український математичний журнал, 2014)
We prove some fixed-point results for multivalued generalized nonlinear contractive mappings in partial metric spaces, which generalize and improve the corresponding recent fixed-point results due to Ćirić [L. B. Ćirić, “Multivalued nonlinear contraction mappings,” Nonlin. Anal., 71, 2716–2723 (2009)] and Klim and Wardowski [D. Klim and D. Wardowski, “Fixed-point theorems for set-valued contractions in complete metric spaces,” J. Math. Anal. Appl., 334, 132–139 (2007)].